Prevalence of HIV in the Eastern Mediterranean Region: A Systematic Review and Meta-Analysis - Saadia Y Alsomali; Mona S Alrehaili; Ghadah Aali Alrashidi (International Journal of Scientific Research and Innovative Studies, 2025)
The Eastern Mediterranean Region (EMR) has historically been considered a low-HIV-prevalence region. However, emerging evidence suggests a rapidly evolving epidemic, with the EMR now identified as one of the few global regions where HIV incidence continues to rise. This systematic review and meta-analysis synthesizes available data on HIV prevalence across the 22 countries of the WHO Eastern Mediterranean Region, with focus on general and key populations. A systematic search was conducted following PRISMA guidelines across PubMed, Scopus, Web of Science, Embase, and regional databases for studies published between January 1990 and December 2023. Random-effects meta-analyses were performed to pool prevalence estimates. Heterogeneity was assessed using I² statistics, and subgroup analyses were conducted by population type and subregion. Among 38,283 screened records, 201 documents met inclusion criteria, with 115 included in meta-analyses. The estimated number of people who inject drugs (PWID) in the EMR was 864,597 (95% CI: 641,909-1,205,255), corresponding to a prevalence of 20.0 per 10,000 adults. Among PWID, the pooled prevalence of HIV was 19.22% (95% CI: 12.86-26.36%), hepatitis C virus 44.82% (29.32-61.16%), and hepatitis B virus 2.66% (0.84-7.26%). Substantial heterogeneity was observed across subregions: South Asia (primarily Pakistan) demonstrated the highest HIV prevalence among PWID at 33.20% (22.00-45.45%), while North Africa showed 8.12% (6.11-10.77%), and other subregions (East Africa, West Asia, Gulf countries) reported prevalence below 1.50%. Among female sex workers (FSW), prevalence ranged from 0-15.7% across countries, and among men who have sex with men (MSM), from 0-12.9%. The total number of people living with HIV (PLHIV) in the EMR was estimated at 530,000-610,000, with only 38% aware of their status and less than one-third receiving antiretroviral treatment. The Eastern Mediterranean Region faces a rapidly growing HIV epidemic, characterized by concentrated epidemics among key populations, particularly PWID in Pakistan and several North African countries. Critical gaps in surveillance, low testing coverage, and underdeveloped harm reduction services threaten epidemic control. Urgent investment in targeted interventions, legal reform, and regional collaboration is required. Keywords: HIV prevalence, Eastern Mediterranean Region, systematic review, meta-analysis, people who inject drugs, key populations, MENA Received Date: February 25, 2025 Accepted Date: March 18, 2025 Published Date: April 01, 2025 Available Online at : https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/634